PRAKTIK PEMBIAYAAN MUDHARABAH PADA BANK JABAR BANTEN (BJB) SYARIAH KCP PATROL INDRAMAYU PERSPEKTIF HUKUM ISLAM - Fikriyatul Fizamani Fitriyah; Irvan Iswandi (Melati Institute, 2023)
Sharia banking is basically a banking system and as a financial institution which upholds the principles contained in the Al-Quran and Hadith. The form of profit sharing products in Islamic banking is Mudharabah Financing, wherein indirect mudharabah financing is a form of rejection of the interest system. With a financing scheme like this, small entrepreneurs can get business capital from Islamic banks with low risk. This study aims to determine the practice of mudharabah financing at Bank Jabar Banten (BJB) Sharia KCP Patrol Indramayu from the Perspective of Islamic Law. This study uses a qualitative approach. The type of research used is a case study (field). The sampling technique in this study used purposive sampling. Primary data was obtained through direct interviews with managers and account officers of BJB Syariah KCP Patrol as well as field observations. Secondary data was obtained through literature and literature studies regarding mudharabah financing practices. The results of this study indicate that in practice there are several stages in the practice of mudharabah financing at BJB Syariah KCP Patrol. Namely among other things from making a financing application, collecting data requirements, interviewing and observing business locations directly, then financing analysis then financing approval by submitting a financing proposal, if financing is permitted, then the process is continued and if it is rejected it cannot be continued, the last stage is making a contract and then the process of disbursing capital from the bank to the customer. In the perspective of Islamic law, the practice of mudharabah financing at BJB Syariah KCP Patrol is seen from the point of view of the principles of fiqh, basically all forms of muamalah are permissible unless there is an argument that forbids it. Then in terms of the pillars and terms of mudharabah financing which is guided by the DSN MUI Fatwa No. 07/DSN-MUI/IV/2000 all pillars and conditions have been fulfilled. Among them are the existence of Aqidaini (the parties who make the contract). consent and qabul, capital, profit ratios, and business activities by the manager (mudharib).